2020
DOI: 10.1055/s-0040-1721399
|View full text |Cite
|
Sign up to set email alerts
|

Usability Testing of a Sensor-Controlled Digital Game to Engage Older Adults with Heart Failure in Physical Activity and Weight Monitoring

Abstract: Background Poor self-management of heart failure (HF) has contributed to poor health outcomes. Sensor-controlled digital games (SCDGs) integrates data from behavior-tracking sensors to trigger progress, rewards, content, and positive feedback in a digital game to motivate real-time behaviors. Objectives To assess the usability of an SCDG prototype over a week of game-playing among 10 older adults with HF in their homes. Methods During initial play, participants' SCDG experiences were observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In brief, from a total of 1524 studies after deleting duplicates, 20 studies were eligible for full-text analysis after reviewing titles and abstracts. After reviewing the full texts, eight studies were included [ 24 , 28 , 29 , 38 , 39 , 40 , 41 , 42 ], and 12 were excluded for the following reasons: no exercise-based CR intervention ( n = 9) [ 22 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], patients with other pathologies were also included ( n = 1) [ 51 ], the patients included were the same as another publication and study design did not fulfill our inclusion criteria ( n = 1) [ 52 ], and lack of information/abstract ( n = 1) [ 53 ]. Although efforts were made to localize unpublished studies, all included studies had been published in peer-reviewed journals.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, from a total of 1524 studies after deleting duplicates, 20 studies were eligible for full-text analysis after reviewing titles and abstracts. After reviewing the full texts, eight studies were included [ 24 , 28 , 29 , 38 , 39 , 40 , 41 , 42 ], and 12 were excluded for the following reasons: no exercise-based CR intervention ( n = 9) [ 22 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ], patients with other pathologies were also included ( n = 1) [ 51 ], the patients included were the same as another publication and study design did not fulfill our inclusion criteria ( n = 1) [ 52 ], and lack of information/abstract ( n = 1) [ 53 ]. Although efforts were made to localize unpublished studies, all included studies had been published in peer-reviewed journals.…”
Section: Resultsmentioning
confidence: 99%
“…Digital literacy is often a concern when digital health interventions are implemented with older adults [ 73 ]. Our study team’s prior experience in conducting usability assessments with older adults with HF as well as in installation of, and training for, devices and apps at the participants’ homes [ 25 ] helped us to design the information and content to support the participants’ self-installation of the apps and use of the devices. Nevertheless, the study might have suffered from selection bias because participation was voluntary and participants already comfortable with using technology might have been especially motivated to participate.…”
Section: Discussionmentioning
confidence: 99%
“…The description of the design, development, and usability assessment phase of the SCDG has been detailed elsewhere [ 25 ]. Guided by the Fogg behavioral model [ 36 ] and played on a smartphone, the Heart Health Mountain SCDG presented a narrative in which the older adult player helps an avatar to climb a mountain in a forested area, with the game’s goal being to avoid hospitalization.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, prior research has indicated that they can also contextualize health behaviors [ 26 ], motivate behavioral changes, and improve health outcomes [ 27 ]. Thus, SCDGs offer an immersive and accessible way to objectively measure self-management behaviors and improve adherence [ 28 ]. Our previous research [ 29 ] conducting an SCDG intervention with 38 adults (aged ≥55 years) with HF from Texas and Oklahoma demonstrated improvements in weight monitoring and physical activity, and the intervention showed a high rate of acceptability (92%) from participants.…”
Section: Introductionmentioning
confidence: 99%